THE EFFECT OF THE AMOUNT OF IMMERSION OF ZnO DOPING Ag THIN LAYER ON BAND GAP WITH DIP COATING METHOD - Farhan El Maulid; - Yohandri; Hary Sanjaya (Department of Physics – Universitas Negeri Padang UNP, 2021)
The availability of fossil energy is decreasing day by day. Therefore, a New Renewable Energy solution is needed. One of the renewable energy is DSSC. DSSC is a photoelectrochemical-based solar cell that has a lower cost, less difficult preparation, and is environmentally friendly. DSSC be composed of working electrode, dye, electrolyte, and counter electrode. This researchintend to investigate the performance of the working electrode where the manufacture of a thin film using the dip coating method with variations in immersion and its effect on the efficiency of DSSC. This research is an experimental research. In this study, the semiconductor working electrode was made based on 9% ZnO/Ag synthesis by going through a sol-gel process. The working electrode was coated with variations of immersion 1, 3 and 5 times. The 9% ZnO/Ag thin layer was characterized by UV-DR Spectrometer. Based on the results, 9% Ag doped ZnO deposited on the ITO substrate with variations of immersion 1, 3 and 5 times showed, a band gap of 3.09 eV, 3.10 eV and 3.12 eV, respectively. Based on these data, it was applied to DSSC with the optimum efficiency shown at the electrode 1 time dip. Therefore, the greater the amount of immersion, the lower the efficiency of the DSSC.The availability of fossil energy is decreasing day by day. Therefore, a New Renewable Energy solution is needed. One of the renewable energy is DSSC. DSSC is a photoelectrochemical-based solar cell that has a lower cost, less difficult preparation, and is environmentally friendly. DSSC be composed of working electrode, dye, electrolyte, and counter electrode. This researchintend to investigate the performance of the working electrode where the manufacture of a thin film using the dip coating method with variations in immersion and its effect on the efficiency of DSSC. This research is an experimental research. In this study, the semiconductor working electrode was made based on 9% ZnO/Ag synthesis by going through a sol-gel process. The working electrode was coated with variations of immersion 1, 3 and 5 times. The 9% ZnO/Ag thin layer was characterized by UV-DR Spectrometer. Based on the results, 9% Ag doped ZnO deposited on the ITO substrate with variations of immersion 1, 3 and 5 times showed, a band gap of 3.09 eV, 3.10 eV and 3.12 eV, respectively. Based on these data, it was applied to DSSC with the optimum efficiency shown at the electrode 1 time dip. Therefore, the greater the amount of immersion, the lower the efficiency of the DSSC.